Efficacy of topical imiquimod in HIV-positive patients with recurrent anal condylomata acuminata - Nadal,Sidney Roberto (2012)
INTRODUCTION: Imiquimod is a topical chemotherapic and immunostimulant agent with antitumoral and antiviral activities, used for anal condylomata acuminata treatment, mainly in recurrences. OBJECTIVE: Evaluate the imiquimod efficiency in chronic and recurrent anal condylomata acuminata in HIV-infected persons. METHOD: A prospective study that analyzed 61 patients with recurrent anal condylomata treated with topic 5% imiquimod, for at least 8 weeks. These patients had already been submitted to other topical and surgical treatments for anal warts. We evaluated the efficiency of this agent, through wart remission, with clinical examination and high-resolution anoscopy, CD4+ T lymphocyte count and side effects. The patients were 55 males and 6 females, from 22 to 63 years old. RESULTS: Remission was seen in 90%, being 46% complete remission and 44% partial remission. Other 10% did not respond to the treatment with imiquimod within the 16th week. Recurrences were observed in 11% of patients in 24-week follow-up. Statistics showed no differences in CD4+ T cell scores when groups with and without complete remission were compared. Adverse effects were reported by 45% of patients. They were mild to moderate burning (25%), intense burning (7%), ulcerative dermatitis (8%) and systemic symptoms (5%). CONCLUSION: Imiquimod was effective in controlling recurrent anal condylomata acuminata in HIV-positive patients, regardless of CD4+ T cell count.